Synthesis, Structural Analysis, and Biological Activities of Some Imidazolium Salts - Gühergül Uluçam; Murat Turkyilmaz (Bioinorganic Chemistry and Applications)
Four newly synthesized imidazolium salts were characterized by nuclear magnetic resonance, vibrational spectra, and mass spectra. Then, the density functional theory calculations were performed to obtain the molecular configurations on which the theoretical nuclear magnetic resonance and infrared spectra were consequently obtained. The comparison of calculated spectra with the experimental spectra for each molecule leads to the conclusion that the theoretical results can be assumed to be a good approach to their molecular configurations. The in vitro biological activities of the salts on the selected bacteria and cancer cell lines were determined by using the broth dilution method according to Clinical and Laboratory Standards Institute guidelines. The 1,3-bis(2-hydroxyethyl) imidazolidinium bromide and 3-(2-ethoxy-2-oxoethly)-1-(3-aminopropyl)-1H-imidazol-3-ium bromide showed efficiency on Bacillus cereus ATCC 11778. The 3-bis(2-carboxyethyl)-4-methyl-1-H-imidazol-3-ium bromide was effective on HeLa while a similar effect was observed on Hep G2 with 3-(2-carboxyethyl)-1-(3-aminopropyl)-1H-imidazol-3-ium bromide.